Heme controls ferroportin1 (FPN1) transcription involving Bach1, Nrf2 and a MARE/ARE sequence motif at position -7007 of the FPN1 promoter - Marro, Samuele; Chiabrando, Deborah; Messana, Erika; Stolte, Jens; Turco, Emilia; Tolosano, Emanuela; Muckenthaler, Martina (Haematologica, the hematology journal, 2010)
Macrophages of the reticuloendothelial system play a key role in recycling iron from hemoglobin of senescent or damaged erythrocytes. Heme oxygenase 1 degrades the heme moiety and releases inorganic iron that is stored in ferritin or exported to the plasma via the iron export protein ferroportin. In the plasma, iron binds to transferrin and is made available for de novo red cell synthesis. The aim of this study was to gain insight into the regulatory mechanisms that control the transcriptional response of iron export protein ferroportin to hemoglobin in macrophages.
Gesehen am 23.05.2023